Bi-metal composite catalyst of copper and rare earth, preparation method of bi-metal composite catalyst and application of bi-metal composite catalyst in electrochemical reduction of carbon dioxide
By using a bimetallic composite catalyst of copper and rare earth and adjusting its molar ratio, the problem of carbon dioxide electrochemical replenishment catalyst in the prior art poor performance in methane current density and selectivity is solved, and efficient selective output of methane or multicarbon products is achieved, and the sub-current density at the industrial level is achieved.
Patent Information
- Application Number
- CN202411962239.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-11
AI Technical Summary
In the prior art, carbon dioxide electrochemical reduction catalysts perform poorly in methane current density and selectivity, and have insufficient stability, so they cannot effectively achieve selective output of different products.
Using a bimetallic composite catalyst of copper and rare earth, the molar ratio of copper salt and rare earth metal salt is adjusted in coordination with the density of mass supplier and surface bond intermediate to achieve selective catalytic production of methane or multicarbon products.
The catalytic activity and selectivity of the catalyst are significantly improved, efficient selective output of methane and multi-carbon products are achieved, and the sub-current density reaches the industrial level and has excellent catalytic effect.
Smart Images

Figure CN119592981A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to electrochemical reduction of carbon dioxide, and in particular to a bimetallic composite catalyst of copper and rare earth, a preparation method thereof and application in electrochemical reduction of carbon dioxide. Background Art
[0002] As global energy demand continues to grow, the increasing consumption of fossil fuels has caused serious environmental pollution and energy crisis. In order to alleviate these problems, people have made great efforts to explore clean energy storage and conversion technologies and reduce environmental pollution, which usually involve various chemical conversion processes. 2 ) electrochemical conversion into dispatchable fuels and value-added chemical feedstocks offers an attractive route to mitigate climate change caused by excess CO2 emissions and addresses the need for seasonal storage of renewable energy. Over the past few decades, efforts have been devoted to developing and promoting electrochemical CO2 reduction reactions to produce carbon-based products, from catalyst design to electrolyte regulation and device engineering. However, generally low energy and carbon efficiencies, as well as suboptimal product selectivity, still severely limit their implementation on an industrial scale.
[0003] CO 2 The electrochemical reduction of carbon to high value-added products usually involves a series of multi-proton / multi-electron transfer reaction processes, which indicates that the reaction pathways are diverse and the product generation mechanism is complex. The surface atoms of the catalyst can be modified by constructing grain boundaries, introducing dopants and defects, which can significantly enhance the bonding between carbon-based intermediates and catalysts, strengthen the adsorption of these intermediates, and provide the possibility of switching to product selectivity. Metal nanoparticle catalysts have been widely used in the field of electrocatalysis. In order to reduce the consumption of precious metals, alloying, crystal face engineering, interface engineering, lattice strain engineering and other technologies are used to further optimize the electrocatalytic performance.
[0004] Currently, CO 2 The research on electrocatalytic reduction is not yet sufficient to reach the industrial level, mainly due to problems such as catalytic activity, catalytic selectivity and catalytic efficiency. CN118727045A discloses a rare earth doped nanoporous copper-based catalyst and its preparation method and application. A certain amount of copper acetate (II) monohydrate and rare earth acetate hydrate are completely dispersed in an isopropanol solvent, and then a certain amount of potassium hydroxide solution is gradually added to completely precipitate it, and finally it is transferred to a polytetrafluoroethylene reactor for solvent thermal reaction, and after it is naturally cooled to room temperature, it is centrifuged, washed, and vacuum dried to obtain the desired catalyst. In a gas diffusion electrode electrolytic cell, the Faraday efficiency of multi-carbon products can reach 62.34%, and the current density exceeds the industrial current density of 200mA / cm 2The preparation method has the advantages of simple steps, no need for special reaction equipment, low energy consumption, high catalytic activity and good stability, and has good prospects for industrial application.
[0005] CN116200757A discloses a Si-doped Cu-based perovskite oxide catalyst and a preparation method thereof, belonging to CO 2 The electrocatalytic technology field comprises the following steps: grinding 2 mol of praseodymium oxide, 0.97 mol of copper oxide, and 0.03 mol of silicon oxide into powder, then mixing the powder with zirconium beads and 100 ml of isopropanol and grinding to obtain a precursor and pouring it into a container, then filtering the zirconium beads in the precursor and drying it to obtain a dry powder, and calcining the dry powder to obtain Pr 2 Cu 0.97 Si 0.03 O 4 -δ(PCSi 0.03 The present invention uses Si-doped Cu-based perovskite catalyst to facilitate the formation of Si-O-Cu bonds, and has good thermodynamic stability and carbon dioxide adsorption capacity. 2 It has very good electro-reduction performance for carbon dioxide in electro-catalytic reduction applications.
[0006] However, the catalysts in the above-mentioned prior art have poor performance for methane current density and low selectivity, and cannot effectively achieve the selective output of different products. Therefore, the research on electrodes is to solve the problem of CO 2 The key to electrocatalytic reduction is that the development of new electrode materials is of great significance for the promotion and application of electrocatalytic processes. Summary of the invention
[0007] The present invention aims to solve the problems of low current density, poor product selectivity and insufficient stability of catalysts for electrochemical reduction of carbon dioxide in producing methane, and provides a bimetallic composite catalyst of copper and rare earth for use in electrochemical reduction of carbon dioxide. The catalyst has high catalytic activity and high selectivity, and can clearly achieve the output of different products by adjusting the molar ratio of copper and rare earth elements.
[0008] To achieve the above object, the technical solution adopted by the present invention is:
[0009] Application of a bimetallic composite catalyst of copper and rare earth in electrochemical reduction of carbon dioxide, wherein the preparation method of the bimetallic composite catalyst comprises the following steps:
[0010] Step 1, mixing copper salt and rare earth metal salt in water, adding ammonium carbonate and inorganic base thereto and stirring for reaction, and centrifuging, washing and drying the mixed solution to obtain a catalyst precursor;
[0011] Step 2, calcining the catalyst precursor to obtain the bimetallic composite catalyst;
[0012] The selective catalytic generation of methane or multi-carbon products from carbon dioxide is achieved by adjusting the molar ratio of the copper salt and the rare earth metal salt in the bimetallic composite catalyst.
[0013] The cooperation of Cu and rare earth metal phases in the present invention induces the formation of different microenvironments, in which the density of local proton donors and surface-bound intermediates can be synergistically adjusted to produce different products. When the Cu content is high, the presence of rare earth metals can promote the generation of proton donors, while the Cu site is conducive to CO 2 Activation and coupling. When the rare earth metal content increases, the presence of rare earth can effectively stabilize copper species, increase the density of proton donors, and facilitate further hydrogenation to generate methane, thereby achieving the selective catalytic generation of methane or multi-carbon products from carbon dioxide by adjusting the molar ratio of copper salt and rare earth metal salt in the bimetallic composite catalyst.
[0014] The inventors have also found that effective product selection can be achieved by regulating the molar ratio of copper salt and rare earth metal salt. When the copper content is high, the selectivity of multi-carbon products in the catalytic product is high and the split flow density is high; when the rare earth element content is high, methane in the catalytic product shows higher selectivity, the split flow density can also reach the industrial level, and the catalytic activity is excellent.
[0015] The molar ratio of the copper salt to the rare earth metal salt is 1:10 to 10:1; for example, it can be 1:10, 1:9, 1:8, 1:7, 1:6, 1:5, 1:4, 1:3, 1:2, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1 or 10:1.
[0016] When the molar ratio of copper salt to rare earth metal salt is 1:1 to 1:10, the Faraday efficiency of methane in the electrochemical reduction reaction of carbon dioxide is above 30%, and the partial current density of methane is 160 mA / cm 2 above;
[0017] Preferably, when the molar ratio of copper salt to rare earth metal salt is 1:3 to 1:10, the Faraday efficiency of methane in the electrochemical reduction reaction of carbon dioxide is above 35%, and the partial current density of methane is above 180 mA / cm 2 above;
[0018] More preferably, when the molar ratio of copper salt to rare earth metal salt is 1:6 to 1:10, the Faraday efficiency of methane in the electrochemical reduction reaction of carbon dioxide is above 50%, and the partial current density of methane is above 250 mA / cm 2 above;
[0019] When the molar ratio of copper salt to rare earth metal salt is 1:1 to 10:1, the Faraday efficiency of the multi-carbon product is above 35%, and the current density is 180 mA / cm 2 above.
[0020] Preferably, when the molar ratio of copper salt to rare earth metal salt is 3:1 to 10:1, the Faraday efficiency of the multi-carbon product is above 40%, and the current density is 220 mA / cm 2 At the same time, the Faraday efficiency and partial current density of methane show a clear downward trend.
[0021] Further preferably, when the molar ratio of copper salt to rare earth metal salt is 6:1 to 10:1, the Faraday efficiency of the multi-carbon product is above 50%, and the current density is 260 mA / cm 2 above.
[0022] The copper salt includes one or more of copper nitrate, sulfate, acetate and chloride salts;
[0023] The rare earth metal salt includes one or more of nitrates, sulfates, acetates and chlorides of rare earth metals; the rare earth metal includes one or more of europium, yttrium, lanthanum, cerium, praseodymium, neodymium or samarium; preferably, the rare earth element is praseodymium.
[0024] The inorganic base includes one or more of potassium hydroxide, sodium hydroxide and cesium hydroxide.
[0025] The (NH 4 ) 2 CO 3 The molar ratio of the inorganic base to the copper salt is 5:1 to 10:1, such as 5:1, 6:1, 7:1, 8:1, 9:1 or 10:1. The molar ratio of the inorganic base to the copper salt is 1:1 to 10:1, such as 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1 or 10:1.
[0026] The mixing and stirring reaction times in step 1 are independently 5-30 minutes; the calcination atmosphere in step 2 is one of air, argon, nitrogen or a hydrogen-argon mixture; the calcination temperature is 300° C. to 800° C., including 300° C., 400° C., 500° C., 600° C., 700° C. or 800° C. The heating rate is 1° C. / min to 10° C. / min; and the calcination time is 1 hour to 6 hours.
[0027] The washing method is one or more of centrifugation or suction filtration. The drying method is one or more of drying or freeze drying.
[0028] In the electrochemical reduction reaction of carbon dioxide, the bimetallic composite catalyst is the working electrode, and the anode is one or more of platinum mesh, foamed Ni, foamed NiO, iridium-plated titanium mesh, and ruthenium-plated titanium mesh;
[0029] The solute of the cathode liquid is selected from KOH, KHCO 3 , KCl, K 2 SO 4 , NaOH, NaHCO 3 , NaCl and Na 2 SO 4 One or more of; the molar concentration of the solute in the cathode liquid is 0.1 to 5.0 mol / L; more preferably, the solute in the cathode liquid is selected from one or both of KOH or NaOH.
[0030] The solute of the anolyte is selected from KHCO 3 , K 2 SO 4 、NaHCO 3 、Na 2 SO 4 , one or more of KOH and NaOH;
[0031] Preferably, a reversible hydrogen electrode is used as a reference electrode, and the relative potential is -4.0 to -0.25 V;
[0032] The current density of the carbon dioxide electrochemical reduction reaction is -1.5 to -0.01 A / cm 2 .
[0033] The present invention also provides a method for preparing a bimetallic composite catalyst of copper and rare earth, comprising the following steps: step 1, mixing a copper salt and a rare earth metal salt in water, adding ammonium carbonate and an inorganic base thereto for stirring and reacting, and centrifuging, washing and drying the mixed solution to obtain a catalyst precursor;
[0034] Step 2: calcining the catalyst precursor to obtain the bimetallic composite catalyst.
[0035] The invention also provides a bimetallic composite catalyst of copper and rare earth prepared according to the preparation method.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] The Cu and rare earth bimetallic composite catalyst in the present invention is used to electro-reduce CO 2 It has high current density, high selectivity, good system stability and long service life. The catalyst has abundant active sites and a large surface area, which can fully interact with the electrolyte and CO 2Contact can overcome the limitation of material transfer. By adjusting the molar ratio of copper and rare earth elements, the selective output of methane or multi-carbon products can be achieved efficiently, and the current density of methane and multi-carbon products has reached the industrial level, with excellent catalytic effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is a SEM image of the microstructure of the CuPr bimetallic composite catalyst prepared in Example 1.
[0039] Figure 2 is the Faraday efficiency of electrocatalytic carbon dioxide production of catalysts with different copper-praseodymium molar ratios.
[0040] Figure 3 This is a diagram of the catalytic stability of the CuPr bimetallic composite catalyst in Example 20. DETAILED DESCRIPTION
[0041] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.
[0042] The raw materials used in the following specific embodiments are all purchased from the market.
[0043] Example 1
[0044] This embodiment provides a method for preparing a Cu and rare earth bimetallic composite catalyst, which specifically comprises the following steps:
[0045] S1. Dissolve 0.5 mmol copper nitrate and 3.0 mmol praseodymium nitrate in 10 mL ultrapure water, mix thoroughly, and stir magnetically to obtain a mixed solution A;
[0046] S2, 12mmol (NH 4 ) 2 CO 3 and 1.5mmol KOH were dissolved in 10mL ultrapure water, mixed thoroughly, and stirred evenly by magnetic stirring to obtain a mixed solution B;
[0047] S3, drip mixed solution B into mixed solution A at a rate of 2 mL / min, and stir magnetically for 10 min;
[0048] S4. The obtained mixed solution is centrifuged, washed, and freeze-dried to obtain a solid precursor.
[0049] S5. calcining the solid precursor at 600° C. for 3 h under an argon atmosphere to obtain a CuPr bimetallic composite catalyst.
[0050] This embodiment also provides an application of a Cu and rare earth bimetallic composite catalyst, using the CuPr bimetallic composite catalyst as a working electrode to reduce CO under constant current. 2 , the applied current density is -0.5A / cm 2 , reaction time 0.5h, CO 2 The flow rate was 20 ml / min, the cathode liquid was 1.0 mol / L KOH solution, the anode liquid was 1.0 mol / L KOH solution, and the counter electrode was nickel foam. CH 4 , H 2 ,CO,C 2 H 4 , CH 3 CH 2 OH, CH 3 CH 2 CH 2 Products such as OH and HCOOH.
[0051] After analyzing the experimental results, CH 4 The Faradaic current efficiency of the product is 61.4%, the Faradaic current efficiency of the multi-carbon product is 12.4%, and the Faradaic current efficiency of the CH 4 The yield was 1.44 mmol / h / cm 2 , CH 4 The current density is 307 mA / cm 2 The partial current density of multi-carbon products is 62 mA / cm 2 , for CH 4 It has good selectivity, especially the partial current density of methane is much higher than that commonly reported in the prior art, and the catalytic effect is excellent.
[0052] The microscopic morphology of the CuPr bimetallic composite catalyst prepared in Example 1 is shown in SEM. Figure 1 As shown, the Faraday efficiency of various products of catalytic carbon dioxide chemical reduction is as follows Figure 2 shown.
[0053] Example 2
[0054] This embodiment provides a preparation method and application of a Cu and rare earth bimetallic composite catalyst, which is different from that of Example 1 in that, in step S1, the added metal salt is 0.5 mmol copper nitrate and 4.5 mmol europium nitrate, and magnetic stirring is performed to obtain a mixed solution. The other steps and methods are the same as those of Example 1, and will not be repeated here, and finally a CuEu bimetallic composite catalyst is obtained.
[0055] Application of a Cu and rare earth bimetallic composite catalyst, using a CuEu bimetallic composite catalyst as a working electrode to reduce CO under constant current 2 , the applied current density is -0.5A / cm 2 , reaction time 0.5h, CO 2 The flow rate was 20 ml / min, the cathode liquid was 1.0 mol / L KOH solution, the anode liquid was 1.0 mol / L KOH solution, and the counter electrode was nickel foam. CH 4 , H 2 ,CO,C 2 H 4 , CH 3 CH 2 OH, CH 3 CH 2 CH 2 Products such as OH and HCOOH.
[0056] After analyzing the experimental results, CH 4 The Faradaic current efficiency of the product is 58.4%, the Faradaic current efficiency of the multi-carbon product is 13.7%, and the 4 The yield was 1.36 mmol / h / cm 2 , CH 4 The current density is 292 mA / cm 2 The partial current density of multi-carbon products is 68.5 mA / cm 2 , for CH 4 There is good selectivity.
[0057] Example 3
[0058] This embodiment provides a preparation method and application of a Cu and rare earth bimetallic composite catalyst, which is different from that of Example 1 in that, in step S1, the metal salt added is 0.5 mmol copper nitrate and 4.5 mmol yttrium nitrate, and magnetic stirring is performed to obtain a mixed solution. The other steps and methods are the same as those of Example 1, and will not be repeated here, and finally a CuY bimetallic composite catalyst is obtained.
[0059] This embodiment also provides an application of a Cu and rare earth bimetallic composite catalyst, using a CuY bimetallic composite catalyst as a working electrode to reduce CO under constant current. 2 , the applied current density is -0.5A / cm 2 , reaction time 0.5h, CO 2 The flow rate was 20 ml / min, the cathode liquid was 1.0 mol / L KOH solution, the anode liquid was 1.0 mol / L KOH solution, and the counter electrode was nickel foam. CH 4 , H 2 ,CO,C2 H 4 , CH 3 CH 2 OH, CH 3 CH 2 CH 2 Products such as OH and HCOOH.
[0060] After analyzing the experimental results, CH 4 The Faradaic current efficiency of the product is 57.4%, the Faradaic current efficiency of the multi-carbon product is 15.9%, and the CH 4 The yield was 1.34 mmol / h / cm 2 , CH 4 The current density is 287 mA / cm 2 The partial current density of multi-carbon products is 79.5 mA / cm 2 , for CH 4 There is good selectivity.
[0061] Example 4
[0062] This embodiment provides a preparation method and application of a Cu and rare earth bimetallic composite catalyst. In step S1, the added metal salt is 0.5 mmol copper nitrate and 4.5 mmol samarium nitrate, and magnetic stirring is performed to obtain a mixed solution. The other steps and methods are the same as those in Example 1, and will not be repeated here, and finally a CuSm bimetallic composite catalyst is obtained.
[0063] This embodiment also provides an application of a Cu and rare earth bimetallic composite catalyst, using the CuSm bimetallic composite catalyst as a working electrode to reduce CO under constant current. 2 , the applied current density is -0.5A / cm 2 , reaction time 0.5h, CO 2 The flow rate was 20 ml / min, the cathode liquid was 1.0 mol / L KOH solution, the anode liquid was 1.0 mol / L KOH solution, and the counter electrode was nickel foam. CH 4 , H 2 ,CO,C 2 H 4 , CH 3 CH 2 OH, CH 3 CH 2 CH 2 Products such as OH and HCOOH.
[0064] After analyzing the experimental results, CH 4 The Faradaic current efficiency of the product is 54.4%, the Faradaic current efficiency of the multi-carbon product is 18.1%, and the 4The yield was 1.28 mmol / h / cm 2 , CH 4 The current density is 272 mA / cm 2 The partial current density of multi-carbon products is 90.5 mA / cm 2 , for CH 4 There is good selectivity.
[0065] Example 5
[0066] This embodiment provides a preparation method and application of a Cu and rare earth bimetallic composite catalyst, which is different from that of Example 1 in that, in step S1, the added metal salt is 0.5 mmol copper nitrate and 4.5 mmol praseodymium nitrate, and the mixed solution is uniformly obtained by magnetic stirring. The other steps and methods are the same as those of Example 1, and will not be repeated here, and finally a CuPr bimetallic composite catalyst is obtained.
[0067] This embodiment also provides an application of a Cu and rare earth bimetallic composite catalyst, using the CuPr bimetallic composite catalyst as a working electrode to reduce CO under constant current. 2 , the applied current density is -0.5A / cm 2 , reaction time 0.5h, CO 2 The flow rate was 20 ml / min, the cathode liquid was 1.0 mol / L KOH solution, the anode liquid was 1.0 mol / L KOH solution, and the counter electrode was nickel foam. CH 4 , H 2 ,CO,C 2 H 4 , CH 3 CH 2 OH, CH 3 CH 2 CH 2 Products such as OH and HCOOH.
[0068] After analyzing the experimental results, CH 4 The Faradaic current efficiency of the product is 52.4%, the Faradaic current efficiency of the multi-carbon product is 8.7%, and the 4 The yield was 1.23 mmol / h / cm 2 , CH 4 The current density is 262 mA / cm 2 The partial current density of multi-carbon products is 43.5 mA / cm 2 , for CH 4 There is good selectivity.
[0069] It can be seen from Examples 2-5 that, at the same molar ratio of copper to rare earth elements, the overall performance of different rare earth elements is very excellent, with high methane selectivity, high current density and high yield.
[0070] Example 6
[0071] This embodiment provides a preparation method and application of a Cu and rare earth bimetallic composite catalyst, which is different from that of Example 1 in that, in step S1, the added metal salt is 0.5 mmol copper nitrate and 1.5 mmol praseodymium nitrate, and the mixed solution is uniformly obtained by magnetic stirring. The other steps and methods are the same as those of Example 1, and will not be repeated here, and finally a CuPr bimetallic composite catalyst is obtained.
[0072] This embodiment also provides an application of a Cu and rare earth bimetallic composite catalyst, using the CuPr bimetallic composite catalyst as a working electrode to reduce CO under constant current. 2 , the applied current density is -0.5A / cm 2 , reaction time 0.5h, CO 2 The flow rate was 20 ml / min, the cathode liquid was 1.0 mol / L KOH solution, the anode liquid was 1.0 mol / L KOH solution, and the counter electrode was nickel foam. CH 4 , H 2 ,CO,C 2 H 4 , CH 3 CH 2 OH, CH 3 CH 2 CH 2 Products such as OH and HCOOH.
[0073] After analyzing the experimental results, CH 4 The Faradaic current efficiency of the product is 37.1%, the Faradaic current efficiency of the multi-carbon product is 32.5%, and the 4 The yield was 0.87 mmol / h / cm 2 , CH 4 The current density is 185.5 mA / cm 2 The partial current density of multi-carbon products is 162.5 mA / cm 2 , for CH 4 There is good selectivity.
[0074] Example 7
[0075] This embodiment provides a preparation method and application of a Cu and rare earth bimetallic composite catalyst, which is different from that of Example 1 in that, in step S1, the added metal salt is 1.5 mmol copper nitrate and 1.5 mmol praseodymium nitrate, and magnetic stirring is performed to obtain a mixed solution. The other steps and methods are the same as those of Example 1, and will not be repeated here, and finally a CuPr bimetallic composite catalyst is obtained.
[0076] This embodiment also provides an application of a Cu and rare earth bimetallic composite catalyst, using a CuPr bimetallic composite catalyst to reduce CO under constant current 2 , the applied current density is -0.5A / cm 2 , reaction time 0.5h, CO 2 The flow rate was 20 ml / min, the cathode liquid was 1.0 mol / L KOH solution, the anode liquid was 1.0 mol / L KOH solution, and the counter electrode was nickel foam. CH 4 , H 2 ,CO,C 2 H 4 , CH 3 CH 2 OH, CH 3 CH 2 CH 2 Products such as OH and HCOOH.
[0077] After analyzing the experimental results, CH 4 The Faradaic current efficiency of CH is 34.4%, and the Faradaic current efficiency of multi-carbon products is 38.1%. 4 The current density is 172 mA / cm 2 The partial current density of multi-carbon products is 190.5 mA / cm 2 .
[0078] Example 8
[0079] This embodiment provides a preparation method and application of a Cu and rare earth bimetallic composite catalyst, which is different from that of Example 1 in that, in step S1, the added metal salt is 1.5 mmol copper nitrate and 0.5 mmol praseodymium nitrate, and the mixed solution is uniformly obtained by magnetic stirring. The other steps and methods are the same as those of Example 1, and will not be repeated here, and finally a CuPr bimetallic composite catalyst is obtained.
[0080] This embodiment also provides an application of a Cu and rare earth bimetallic composite catalyst, using the CuPr bimetallic composite catalyst as a working electrode to reduce CO under constant current. 2 , the applied current density is -0.5A / cm 2 , reaction time 0.5h, CO 2The flow rate was 20 ml / min, the cathode liquid was 1.0 mol / L KOH solution, the anode liquid was 1.0 mol / L KOH solution, and the counter electrode was nickel foam. CH 4 , H 2 ,CO,C 2 H 4 , CH 3 CH 2 OH, CH 3 CH 2 CH 2 Products such as OH and HCOOH.
[0081] After analyzing the experimental results, CH 4 The Faradaic current efficiency of the product is 24.7%, the Faradaic current efficiency of the multi-carbon product is 46.7%, and the 4 The current density is 123.5 mA / cm 2 The partial current density of multi-carbon products is 233.5 mA / cm 2 , with good selectivity for multi-carbon products.
[0082] Example 9
[0083] This embodiment provides a preparation method and application of a Cu and rare earth bimetallic composite catalyst, which is different from that of Example 1 in that, in step S1, the added metal salt is 3.0 mmol copper nitrate and 0.5 mmol praseodymium nitrate, and the mixed solution is uniformly obtained by magnetic stirring. The other steps and methods are the same as those of Example 1, and will not be repeated here, and finally a CuPr bimetallic composite catalyst is obtained.
[0084] This embodiment also provides an application of a Cu and rare earth bimetallic composite catalyst, using the CuPr bimetallic composite catalyst as a working electrode to reduce CO under constant current. 2 , the applied current density is -0.5A / cm 2 , reaction time 0.5h, CO 2 The flow rate was 20 ml / min, the cathode liquid was 1.0 mol / L KOH solution, the anode liquid was 1.0 mol / L KOH solution, and the counter electrode was nickel foam. CH 4 , H 2 ,CO,C 2 H 4 , CH 3 CH 2 OH, CH 3 CH 2 CH 2 Products such as OH and HCOOH.
[0085] After analyzing the experimental results, CH 4The Faradaic current efficiency of the product is 14.8%, the Faradaic current efficiency of the multi-carbon product is 58.9%, and the 4 The current density is 74 mA / cm 2 The partial current density of multi-carbon products is 294.5 mA / cm 2 , with good selectivity for multi-carbon products.
[0086] Example 10
[0087] This embodiment provides a preparation method and application of a Cu and rare earth bimetallic composite catalyst, which is different from that of Example 1 in that, in step S1, the added metal salt is 4.5 mmol copper nitrate and 0.5 mmol praseodymium nitrate, and the mixed solution is uniformly obtained by magnetic stirring. The other steps and methods are the same as those of Example 1, and will not be repeated here, and finally a CuPr bimetallic composite catalyst is obtained.
[0088] This embodiment also provides an application of a Cu and rare earth bimetallic composite catalyst, using the CuPr bimetallic composite catalyst as a working electrode to reduce CO under constant current. 2 , the applied current density is -0.5A / cm 2 , reaction time 0.5h, CO 2 The flow rate was 20 ml / min, the cathode liquid was 1.0 mol / L KOH solution, the anode liquid was 1.0 mol / L KOH solution, and the counter electrode was nickel foam. CH 4 , H 2 ,CO,C 2 H 4 , CH 3 CH 2 OH, CH 3 CH 2 CH 2 OH and HCOOH. After analyzing the experimental results, CH 4 The Faradaic current efficiency of the product is 11.2%, the Faradaic current efficiency of the multi-carbon product is 67.8%, and the 4 The current density is 56 mA / cm 2 The partial current density of multi-carbon products is 339 mA / cm 2 , with good selectivity for multi-carbon products.
[0089] The Faraday efficiencies of different products of the catalysts of Example 1 and Examples 5-10 are as follows: Figure 2As shown, the catalysts obtained under different molar ratios of copper and rare earth elements show significantly different selectivities for the products of the electrochemical reduction reaction of carbon dioxide. When the copper content is high, the catalyst catalyzes the reduction of carbon dioxide and shows a high selectivity for multi-carbon products, especially when the molar ratio of copper to rare earth elements is above 6:1; when the copper content is lower than that of rare earth elements, the catalyst catalyzes the reduction of carbon dioxide and shows a high selectivity for methane, and the partial current density effect of methane is very excellent.
[0090] Embodiment 11
[0091] This embodiment provides a preparation method and application of a Cu and rare earth bimetallic composite catalyst, which is different from that of embodiment 1 in that, in step S2, 15 mmol (NH 4 ) 2 CO 3 and 1.5 mmol KOH were dissolved in 10 mL ultrapure water and mixed thoroughly to obtain a mixed solution. The other steps and methods were the same as those in Example 1 and will not be described again, and finally a CuPr bimetallic composite catalyst was obtained.
[0092] This embodiment also provides an application of a Cu and rare earth bimetallic composite catalyst, using the CuPr bimetallic composite catalyst as a working electrode to reduce CO under constant current. 2 , the applied current density is -0.5A / cm 2 , reaction time 0.5h, CO 2 The flow rate was 20 ml / min, the cathode liquid was 1.0 mol / L KOH solution, the anode liquid was 1.0 mol / L KOH solution, and the counter electrode was nickel foam. CH 4 , H 2 ,CO,C 2 H 4 , CH 3 CH 2 OH, CH 3 CH 2 CH 2 Products such as OH and HCOOH.
[0093] After analyzing the experimental results, CH 4 The Faradaic current efficiency of the product is 56.2%, the Faradaic current efficiency of the multi-carbon product is 17.8%, and the CH 4 The yield was 1.32 mmol / h / cm 2 , CH 4 The current density is 281 mA / cm 2 The partial current density of multi-carbon products is 89 mA / cm 2 , with good selectivity for methane products.
[0094] Example 12
[0095] This embodiment provides a preparation method and application of a Cu and rare earth bimetallic composite catalyst, which is different from that of embodiment 1 in that, in step S2, 9 mmol (NH 4 ) 2 CO 3 and 1.5 mmol KOH were dissolved in 10 mL ultrapure water and mixed thoroughly to obtain a mixed solution. The other steps and methods were the same as those in Example 1 and will not be described again, and finally a CuPr bimetallic composite catalyst was obtained.
[0096] This embodiment also provides an application of a Cu and rare earth bimetallic composite catalyst, using the CuPr bimetallic composite catalyst as a working electrode to reduce CO under constant current. 2 , the applied current density is -0.5A / cm 2 , reaction time 0.5h, CO 2 The flow rate was 20 ml / min, the cathode liquid was 1.0 mol / L KOH solution, the anode liquid was 1.0 mol / L KOH solution, and the counter electrode was nickel foam. CH 4 , H 2 ,CO,C 2 H 4 , CH 3 CH 2 OH, CH 3 CH 2 CH 2 Products such as OH and HCOOH.
[0097] After analyzing the experimental results, CH 4 The Faradaic current efficiency of the product is 54.7%, the Faradaic current efficiency of the multi-carbon product is 19.4%, and the 4 The yield was 1.28 mmol / h / cm 2 , CH 4 The current density is 273.5 mA / cm 2 The partial current density of multi-carbon products is 97 mA / cm 2 , with good selectivity for methane products.
[0098] Example 13
[0099] This embodiment provides a preparation method and application of a Cu and rare earth bimetallic composite catalyst, which is different from that of Example 1 in that, in step S3, the mixed solution B is dripped into the mixed solution A at a rate of 5 mL / min, and magnetic stirring is performed for 10 min. The other steps and methods are the same as those of Example 1, and will not be repeated here, and finally a CuPr bimetallic composite catalyst is obtained.
[0100] This embodiment also provides an application of a Cu and rare earth bimetallic composite catalyst, using the CuPr bimetallic composite catalyst as a working electrode to reduce CO under constant current. 2 , the applied current density is -0.5A / cm 2 , reaction time 0.5h, CO 2 The flow rate was 20 ml / min, the cathode liquid was 1.0 mol / L KOH solution, the anode liquid was 1.0 mol / L KOH solution, and the counter electrode was nickel foam. CH 4 , H 2 ,CO,C 2 H 4 , CH 3 CH 2 OH, CH 3 CH 2 CH 2 Products such as OH and HCOOH.
[0101] After analyzing the experimental results, CH 4 The Faradaic current efficiency of the product is 60.7%, the Faradaic current efficiency of the multi-carbon product is 13.7%, and the CH 4 The yield was 1.42 mmol / h / cm 2 , CH 4 The current density is 303.5 mA / cm 2 The partial current density of multi-carbon products is 68.7 mA / cm 2 , with good selectivity for methane products.
[0102] Embodiment 14
[0103] This embodiment provides a preparation method and application of a Cu and rare earth bimetallic composite catalyst, which is different from that of Example 1 in that, in step S3, the mixed solution B is dripped into the mixed solution A at a rate of 1 mL / min, and magnetic stirring is performed for 10 min. The other steps and methods are the same as those of Example 1, and will not be repeated here, and finally a CuPr bimetallic composite catalyst is obtained.
[0104] This embodiment also provides an application of a Cu and rare earth bimetallic composite catalyst, using the CuPr bimetallic composite catalyst as a working electrode to reduce CO under constant current. 2 , the applied current density is -0.5A / cm 2 , reaction time 0.5h, CO 2 The flow rate was 20 ml / min, the cathode liquid was 1.0 mol / L KOH solution, the anode liquid was 1.0 mol / L KOH solution, and the counter electrode was nickel foam. CH 4 , H 2 ,CO,C 2H 4 , CH 3 CH 2 OH, CH 3 CH 2 CH 2 Products such as OH and HCOOH.
[0105] After analyzing the experimental results, CH 4 The Faradaic current efficiency of the product is 60.5%, the Faradaic current efficiency of the multi-carbon product is 12.8%, and the Faradaic current efficiency of the CH 4 The yield was 1.41 mmol / h / cm 2 , CH 4 The current density is 302.5 mA / cm 2 The partial current density of multi-carbon products is 64 mA / cm 2 , with good selectivity for methane products.
[0106] Embodiment 15
[0107] This embodiment provides a preparation method and application of a Cu and rare earth bimetallic composite catalyst, which is different from that of Embodiment 1 in that, in step S4, the mixed solution is filtered and dried overnight at 60° C. The other steps and methods are the same as those of Embodiment 1 and will not be described again, and finally a CuPr bimetallic composite catalyst is obtained.
[0108] This embodiment also provides an application of a Cu and rare earth bimetallic composite catalyst, using the CuPr bimetallic composite catalyst as a working electrode to reduce CO under constant current. 2 , the applied current density is -0.5A / cm 2 , reaction time 0.5h, CO 2 The flow rate was 20 ml / min, the cathode liquid was 1.0 mol / L KOH solution, the anode liquid was 1.0 mol / L KOH solution, and the counter electrode was nickel foam. CH 4 , H 2 ,CO,C 2 H 4 , CH 3 CH 2 OH, CH 3 CH 2 CH 2 Products such as OH and HCOOH.
[0109] After analyzing the experimental results, CH 4 The Faradaic current efficiency of the product is 58.9%, the Faradaic current efficiency of the multi-carbon product is 11.8%, and the Faradaic current efficiency of the CH 4 The yield was 1.37 mmol / h / cm 2 , CH 4The current density is 294.5 mA / cm 2 The partial current density of multi-carbon products is 59 mA / cm 2 , with good selectivity for methane products.
[0110] Example 16
[0111] This embodiment provides a preparation method and application of a Cu and rare earth bimetallic composite catalyst, which is different from that of Example 1 in that, in step S5, the solid precursor is calcined at 800° C. for 3 h under an argon atmosphere to obtain a bimetallic composite catalyst. The other steps and methods are the same as those of Example 1 and will not be repeated here, and finally a CuPr bimetallic composite catalyst is obtained.
[0112] This embodiment also provides an application of a Cu and rare earth bimetallic composite catalyst, using the CuPr bimetallic composite catalyst as a working electrode to reduce CO under constant current. 2 , the applied current density is -0.5A / cm 2 , reaction time 0.5h, CO 2 The flow rate was 20 ml / min, the cathode liquid was 1.0 mol / L KOH solution, the anode liquid was 1.0 mol / L KOH solution, and the counter electrode was nickel foam. CH 4 , H 2 ,CO,C 2 H 4 , CH 3 CH 2 OH, CH 3 CH 2 CH 2 Products such as OH and HCOOH.
[0113] After analyzing the experimental results, CH 4 The Faradaic current efficiency of the product is 58.4%, the Faradaic current efficiency of the multi-carbon product is 12.1%, and the Faradaic current efficiency of the CH 4 The yield was 1.36 mmol / h / cm 2 , CH 4 The current density is 292 mA / cm 2 The partial current density of multi-carbon products is 60.5 mA / cm 2 , with good selectivity for methane products.
[0114] Embodiment 17
[0115] This embodiment provides a preparation method and application of a Cu and rare earth bimetallic composite catalyst, which is different from that of Example 1 in that, in step S5, the solid precursor is calcined at 300° C. for 3 h under an argon atmosphere to obtain a bimetallic composite catalyst. The other steps and methods are the same as those of Example 1 and will not be repeated here, and finally a CuPr bimetallic composite catalyst is obtained.
[0116] This embodiment also provides an application of a Cu and rare earth bimetallic composite catalyst, using the CuPr bimetallic composite catalyst as a working electrode to reduce CO under constant current. 2 , the applied current density is -0.5A / cm 2 , reaction time 0.5h, CO 2 The flow rate was 20 ml / min, the cathode liquid was 1.0 mol / L KOH solution, the anode liquid was 1.0 mol / L KOH solution, and the counter electrode was nickel foam. CH 4 , H 2 ,CO,C 2 H 4 , CH 3 CH 2 OH, CH 3 CH 2 CH 2 Products such as OH and HCOOH.
[0117] After analyzing the experimental results, CH 4 The Faradaic current efficiency of the product is 54.7%, the Faradaic current efficiency of the multi-carbon product is 19.7%, and the 4 The yield was 1.28 mmol / h / cm 2 , CH 4 The current density is 273.5 mA / cm 2 The partial current density of multi-carbon products is 98.5 mA / cm 2 , with good selectivity for methane products.
[0118] Embodiment 18
[0119] This embodiment provides a preparation method and application of a Cu and rare earth bimetallic composite catalyst.
[0120] The difference from Example 1 is that in step S5, the solid precursor is calcined at 600° C. for 1 h under an argon atmosphere to obtain a bimetallic composite catalyst. The other steps and methods are the same as those in Example 1 and will not be repeated here, and finally a CuPr bimetallic composite catalyst is obtained.
[0121] This embodiment also provides an application of a Cu and rare earth bimetallic composite catalyst, using a CuPr bimetallic composite catalyst to reduce CO under constant current2 , the applied current density is -0.5A / cm 2 , reaction time 0.5h, CO 2 The flow rate was 20 ml / min, the cathode liquid was 1.0 mol / L KOH solution, the anode liquid was 1.0 mol / L KOH solution, and the counter electrode was nickel foam. CH 4 , H 2 ,CO,C 2 H 4 , CH 3 CH 2 OH, CH 3 CH 2 CH 2 OH and HCOOH. After analyzing the experimental results, CH 4 The Faradaic current efficiency of the product is 55.3%, the Faradaic current efficiency of the multi-carbon product is 15.4%, and the Faradaic current efficiency of the CH 4 The yield was 1.29 mmol / h / cm 2 , CH 4 The current density is 276.5 mA / cm 2 The partial current density of multi-carbon products is 77 mA / cm 2 , with good selectivity for methane products.
[0122] Embodiment 19
[0123] This embodiment provides a preparation method and application of a Cu and rare earth bimetallic composite catalyst.
[0124] The difference from Example 1 is that in step S5, the solid precursor is calcined at 600° C. for 6 h under an argon atmosphere to obtain a bimetallic composite catalyst. The other steps and methods are the same as those in Example 1 and will not be repeated here, and finally a CuPr bimetallic composite catalyst is obtained.
[0125] This embodiment also provides an application of a Cu and rare earth bimetallic composite catalyst, using a CuPr bimetallic composite catalyst to reduce CO under constant current 2 , the applied current density is -0.5A / cm 2 , reaction time 0.5h, CO 2 The flow rate was 20 ml / min, the cathode liquid was 1.0 mol / L KOH solution, the anode liquid was 1.0 mol / L KOH solution, and the counter electrode was nickel foam. CH 4 , H 2 ,CO,C 2 H 4 , CH 3 CH 2 OH, CH 3 CH2 CH 2 OH and HCOOH. After analyzing the experimental results, CH 4 The Faradaic current efficiency of the product is 60.7%, the Faradaic current efficiency of the multi-carbon product is 11.5%, and the 4 The yield was 1.42 mmol / h / cm 2 , CH 4 The current density is 303.5 mA / cm 2 The partial current density of multi-carbon products is 57.5 mA / cm 2 , with good selectivity for methane products.
[0126] Embodiment 20
[0127] This example provides a long-term performance test of a Cu and rare earth bimetallic composite catalyst.
[0128] The preparation method of this embodiment is the same as that of embodiment 1, except that the applied current density is -0.2A / cm 2 In the long-term performance test of more than 5 hours, the exhaust gas of the cathode chamber was measured by online gas chromatography to quantitatively determine the gas products. Figure 3 shown.
[0129] like Figure 3 As shown, the CuPr bimetallic composite catalyst obtained in Example 1 was used to carry out CO 2 Electrochemical reduction, at -0.2A / cm 2 Under the current density of , CH 4 The Faraday efficiency changes very little, which shows that the performance of the catalyst has almost no attenuation and good stability.
Claims
1. Application of a bimetallic composite catalyst of copper and rare earth in electrochemical reduction of carbon dioxide, characterized in that: The preparation method of the bimetallic composite catalyst comprises the steps of: Step 1, mixing copper salt and rare earth metal salt in water, adding ammonium carbonate and inorganic base thereto and stirring for reaction, and centrifuging, washing and drying the mixed solution to obtain a catalyst precursor; Step 2, calcining the catalyst precursor to obtain the bimetallic composite catalyst; The selective catalytic generation of methane or multi-carbon products from carbon dioxide is achieved by adjusting the molar ratio of the copper salt and the rare earth metal salt in the bimetallic composite catalyst.
2. The use of the bimetallic composite catalyst of copper and rare earth in electrochemical reduction of carbon dioxide according to claim 1, characterized in that: The molar ratio of the copper salt to the rare earth metal salt is 1:10 to 10:1; When the molar ratio of copper salt to rare earth metal salt is 1:1 to 1:10, the Faraday efficiency of methane in the electrochemical reduction reaction of carbon dioxide is above 30%, and the partial current density of methane is 160 mA / cm 2 above; When the molar ratio of copper salt to rare earth metal salt is 1:1 to 10:1, the Faraday efficiency of the multi-carbon product is above 35%, and the current density is 180 mA / cm 2 above.
3. The use of the bimetallic composite catalyst of copper and rare earth in electrochemical reduction of carbon dioxide according to claim 1, characterized in that: The copper salt includes one or more of copper nitrate, sulfate, acetate and chloride salts; The rare earth metal salt includes one or more of nitrates, sulfates, acetates and chlorides of rare earth metals; the rare earth metal includes one or more of europium, yttrium, lanthanum, cerium, praseodymium, neodymium or samarium; The inorganic base includes one or more of potassium hydroxide, sodium hydroxide and cesium hydroxide.
4. The use of the bimetallic composite catalyst of copper and rare earth in electrochemical reduction of carbon dioxide according to claim 1, characterized in that: The molar ratio of the (NH4)2CO3 to the inorganic base is 5:1 to 10:1; the molar ratio of the inorganic base to the copper salt is 1:1 to 10:
1.
5. The use of the bimetallic composite catalyst of copper and rare earth in electrochemical reduction of carbon dioxide according to claim 1, characterized in that: The mixing and stirring reaction times in step 1 are independently 5-30 minutes; the calcination atmosphere in step 2 is one of air, argon, nitrogen or a hydrogen-argon mixture; the calcination temperature is 300°C to 800°C, the heating rate is 1°C / min to 10°C / min; and the calcination time is 1h to 6h.
6. The use of the bimetallic composite catalyst of copper and rare earth in electrochemical reduction of carbon dioxide according to claim 1, characterized in that: In the electrochemical reduction reaction of carbon dioxide, the bimetallic composite catalyst is the working electrode, and the anode is one or more of platinum mesh, Ni foam, NiO foam, iridium-plated titanium mesh, and ruthenium-plated titanium mesh; The solute of the cathode liquid is selected from one or more of KOH, KHCO3, KCl, K2SO4, NaOH, NaHCO3, NaCl and Na2SO4; the molar concentration of the solute in the cathode liquid is 0.1 to 5.0 mol / L; The solute of the anolyte is selected from one or more of KHCO3, K2SO4, NaHCO3, Na2SO4, KOH and NaOH; The current density of the carbon dioxide electrochemical reduction reaction is -1.5 to -0.01 A / cm 2 .
7. A method for preparing a bimetallic composite catalyst of copper and rare earth, characterized in that: The method comprises the following steps: step 1, mixing copper salt and rare earth metal salt in water, adding ammonium carbonate and inorganic base thereto for stirring reaction, and centrifuging, washing and drying the mixed solution to obtain a catalyst precursor; Step 2: calcining the catalyst precursor to obtain the bimetallic composite catalyst.
8. The method for preparing a bimetallic composite catalyst of copper and rare earth according to claim 7, characterized in that: The molar ratio of the copper salt to the rare earth metal salt is 1:10 to 10:1; The molar ratio of (NH4)2CO3 to the inorganic base is 5:1 to 10:1; the molar ratio of the inorganic base to the copper salt is 1:1 to 10:1; The mixing and stirring reaction times in step 1 are independently 5-30 minutes; the calcination atmosphere in step 2 is one of air, argon, nitrogen or a hydrogen-argon mixture; the calcination temperature is 300°C to 800°C, the heating rate is 1°C / min to 10°C / min; and the calcination time is 1h to 6h.
9. The method for preparing a bimetallic composite catalyst of copper and rare earth according to claim 7, characterized in that: The rare earth metal includes one or more of europium, yttrium, lanthanum, cerium, praseodymium, neodymium or samarium.
10. A bimetallic composite catalyst of copper and rare earth prepared according to the preparation method according to any one of claims 7 to 9.
Citation Information
Cited By
Perfluoropolyether-containing composite electrode for electrocatalytic carbon dioxide reduction and preparation method thereof
CN120738704A
A composite electrode for electrocatalytic carbon dioxide reduction containing perfluoropolyether and a preparation method thereof
CN120738704B
Preparation method of copper-based composite catalyst and application of copper-based composite catalyst in CO2 electrocatalytic reduction
CN121362994A
Preparation method and application of copper-rare earth metal bimetallic composite catalytic material
CN122466506A